Special Issue “Advances in Aerial, Space, and Underwater Robotics” - Silvio Cocuzza; Alberto Doria; Benedetto Allotta (Applied Sciences, 2022)
Free-base robotic systems are extensively used in underwater, air, and space environments [...]